ChemInform Abstract: A Catalytic Enantiotopic‐Group‐Selective Suzuki Reaction for the Construction of Chiral Organoboronates. Issue 47 (6th November 2014) - Sun, Chunrui; Potter, Bowman; Morken, James P.
Abstract The conversion of achiral geminal bis(pinacolboronates) into chiral organoboronates proceeds in the presence of a chiral monodentate taddol‐derived phosphoramidite ligand and occurs with high enantioselectivity.